2004
DOI: 10.1023/b:card.0000033645.55138.3d
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Effects on Intima Media Thickness: An Evaluation of Rosuvastatin in Subclinical Atherosclerosis—The Rationale and Methodology of the METEOR Study

Abstract: Summary. Background: Increased carotid intima media thickness (IMT) is associated with established coronary heart disease (CHD) and is a marker of atherosclerosis.Statins are an effective treatment for dyslipidaemia, and have been shown to retard progression or promote carotid IMT regression in patients at high risk of CHD. Rosuvastatin is a highly efficacious statin, and the Measuring Effects on intima media Thickness: an Evaluation Of Rosuvastatin (METEOR) study is designed to assess the impact of rosuvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 47 publications
0
47
1
2
Order By: Relevance
“…The rationale, study design and main results of METEOR have been reported in detail before [18,19]. In summary, METEOR was a randomized, double-blind, placebocontrolled trial designed to assess the impact of rosuvastatin 40 mg daily versus placebo on the rate of change in CIMT over 2 years of follow-up.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale, study design and main results of METEOR have been reported in detail before [18,19]. In summary, METEOR was a randomized, double-blind, placebocontrolled trial designed to assess the impact of rosuvastatin 40 mg daily versus placebo on the rate of change in CIMT over 2 years of follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…Ultrasound images were taken from three predefined carotid segments: the common carotid artery, the carotid bifurcation and the internal carotid artery, each providing near and far wall data for the right and left carotid arteries. Real-time image sequences of these 12 artery segments were collected from five circumferential angles and recorded to SVHS videotape and shipped to one of the two regional CIMT core laboratories for offline reading as described before [18].…”
Section: B-mode Ultrasound Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a landmark paper by O'Leary et al (5), increases in carotid IMT were directly associated with an increased risk of myocardial infarction and stroke in older adults with no history of cardiovascular disease. Consequently, carotid IMT has emerged as a marker for cardiovascular disease (6) and has been used as an endpoint in clinical trials assessing the effect of pharmacological treatment of systemic atherosclerosis (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The rationale, design, and main findings of METEOR have been reported in detail previously 21,22) . In essence, METEOR was a randomized, doubleblind, placebo-controlled trial among 984 individuals from Europe and North America.…”
Section: Study Populationmentioning
confidence: 99%